GLP-1 Relaxes Rat Coronary Arteries by Enhancing ATP-Sensitive Potassium Channel Currents - Qian-Feng Xiong; Shao-Hua Fan; Xue-Wen Li; Yu Niu; Jing Wang; Xin Zhang; Yi-Fan Chen; Ya-Wei Shi; Li-Hui Zhang (Cardiology Research and Practice)
GLP-1 is a new type of antidiabetic agent that possesses many beneficial effects. Although its cardiovascular actions have been widely examined, little is known about GLP-1’s effects on the rat coronary artery (RCA) or about the mechanisms underpinning these effects. Here, we report that GLP-1 inhibits depolarization- or thromboxane receptor agonist (U46619)-induced RCA contraction in a dosage-dependent manner. Vasorelaxation was attenuated by denuding the endothelium, L-NAME (nitric oxide synthase inhibitor), and glyburide (KATP channel blocker) but was not affected by indomethacin (cyclooxygenase inhibitor), iberiotoxin [Ca2+-activated K+ channel (KCa) blocker], or 4-aminopyridine (KV channel blocker). Furthermore, GLP-1 increased outward K+ currents by enhancing the KATP channel in rat coronary arterial smooth muscle cells (RCASMCs). These results show that GLP-1 is an endothelial-dependent vasospasmolytic agent in the RCA and imply that the relaxant effect is regulated by enhancing KATP rather than KV or KCa currents in RCASMCs.